Biomimetic Bacterial Identification Platform Based on Thermal Transport Analysis Through Surface Imprinted Polymers: From Proof of Principle to Proof of Application. Issue 12 (19th August 2010) - Heidt, Benjamin; Rogosic, Renato; Lowdon, Joseph W.; Desmond‐Kennedy, Muriel; Jurgaityte, Kaste; Ferrer Orri, Jordi; Kronshorst, Yara; Mendez, Stephanie; Polyakova, Elizaveta; Rice, Henry T.; Crijns, Francy; Diliën, Hanne; et al.
Abstract : Accurate and sensitive detection of bacteria is crucial in medicine for diagnosis and effective treatment of infectious diseases. Current state‐of‐the art methods consist of either traditional time consuming microbiological analysis or rapid, sensitive molecular techniques that require expensive readout equipment. In previous work, the authors of this paper combined synthetic bacteria receptors, so‐called surface imprinted polymers (SIPs), with a novel thermal biosensor readout methodology for the detection of bacteria in urine. In this follow‐up study, the potential of the method for application in urinary tract infection (UTI) diagnosis is further studied. The reproducibility of the method is assessed by expanding the study and analyzing the sensor's performance in urine samples obtained from four healthy adults. The samples are spiked with increasing concentrations of Escherichia coli to obtain different dose‐response curves. The results of this study show that the method is reproducible over the studied population and variables such as age, gender and osmolality do not seem to influence the test. All results fall within the previously established dynamic range of 10 4 –10 5 bacteria mL −1 which fits well within the diagnostic window of classical microbiological UTI tests. Further tests conducted on a urine sample 24 h after spiking illustrate the problem with traditional microbiology tests as the sensor response has significantly decreased due to the presence of a significant amount of dead bacteria in the day‐old sample. These results confirm that fast, point‐of‐care analysis of fresh urine samples is advantageous over classic laborious techniques in terms of accurate diagnosis. Abstract : This paper further explores the potential of a recently developed thermal biosensor platform for point‐of‐care bacteria detection. The sensor essentially combines highly selective synthetic cell receptors (surface imprinted polymers or SIPs) with a low‐cost readout technique (the heat‐transfer method or HTM) to detect bacteria in urine samples from different volunteers in diagnostically relevant concentrations.